2001
DOI: 10.1161/01.cir.103.20.2508
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Gradients in Shear, but Not Spatial Gradients, Stimulate Endothelial Cell Proliferation

Abstract: Background —The effect of temporal and spatial gradients in shear on primary human endothelial cell (HUVEC) proliferation was investigated. The sudden-expansion flow chamber (SEFC) model was used to differentiate the effect of temporal gradients in shear from that of spatial gradients. With a sudden onset of flow, cells are exposed to both temporal and spatial gradients of shear. The temporal gradients can be eliminated by slowly ramping up the flow. Methods and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 18 publications
12
115
0
2
Order By: Relevance
“…The HSSGs examined in this study vary from 0 to Ϸ2,500 dyne͞cm 2 per cm (1 dyne ϭ 10 N) and are Ͼ1 order of magnitude greater than other flow chamber designs (17) and closer to those observed near arterial bifurcations and branch sites (1,18). These high shear gradients are of special interest in atherogenesis, because it has been proposed that these regions are prone to lesion development (3,19,20). The present study attempts to explain these various observations within the context of a new mechanical model for the actin cytoskeleton.…”
mentioning
confidence: 58%
“…The HSSGs examined in this study vary from 0 to Ϸ2,500 dyne͞cm 2 per cm (1 dyne ϭ 10 N) and are Ͼ1 order of magnitude greater than other flow chamber designs (17) and closer to those observed near arterial bifurcations and branch sites (1,18). These high shear gradients are of special interest in atherogenesis, because it has been proposed that these regions are prone to lesion development (3,19,20). The present study attempts to explain these various observations within the context of a new mechanical model for the actin cytoskeleton.…”
mentioning
confidence: 58%
“…While human in vivo studies typically describe shear stress as a mean construct, numerous secondary phenomena associated with flow, including pulsatile flow, retrograde flow, and flow turbulence, can influence the regulation of endothelial cells [67][68][69][70][71][72] .…”
Section: Importance Of the Velocity Profilementioning
confidence: 99%
“…5). In vitro studies suggest that these two distinct fluid stimuli (velocity acceleration vs. steady shear) regulate short-and longterm endothelial function via independent biomechanical pathways 70,71,[73][74][75] . Studies have shown that the rate of velocity acceleration can affect the progression of atherosclerosis 70,73,76) , endothelial cell function 71 , 74) , mechanotransduction 77,78) , calcium kinetics 79,80) , and vascular tone 81,82) .…”
Section: Velocity Acceleration and Endothelial Functionmentioning
confidence: 99%
“…Shear-induced signaling cascades and changes in endothelial cell morphology have been reviewed extensively (20,21,55). Shear stress can induce changes in endothelial cell proliferation (92), membrane fluidity (9), and cell morphology (62,96).…”
Section: Techniques For Mechanically Probing Cellsmentioning
confidence: 99%